MODERN APPROACHES TO CONFLICT MANAGEMENT IN HOTEL AND RESTAURANT BUSINESS ESTABLISHMENTS - RUDNICHENKO, Yevgenii; DAVYDOVA, Olena; SULIMA, Viktoriya (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article examines the essence and features of conflicts. Conflicts should be understood as a complex phenomenon that can be caused by various circumstances, contradictions between two or more parties, and is accompanied by mutual actions or disagreements and can have various consequences. The main features of conflict are given, which include: contradiction, mutual disagreement, interaction, tension, desire for influence and the need for a solution. The existing conflict theories were studied, in particular within the framework of systems theory (conflicts arise as a result of disagreements and imbalances in systems, in particular social, political and economic), functionalist theory (conflicts are considered as a normal and necessary part of social life) and social-psychological theory (conflicts arise as a result of disagreements interests (individual, group and intergroup). The main advantages and disadvantages of the considered theories are given. With the development of the theory of conflicts, their essence and meaning were rethought and considered from different points of view. It should be noted that until the 20th century, conflict was considered as an exclusively negative phenomenon, however , after the 20th century, views on its essence have changed, and it is considered from the point of view of positive content, which contributes not only to problems in the activities of organizations, but also to their development. Conflicts between guests and employees result in the form of various complaints, which are divided into the following categories: complaints about service, complaints about cleanliness and hygiene, complaints about technical problems, complaints about the quality of food in the establishment, complaints about accommodation and comfort, etc. The article lists the main conflict generators by manifestation and behavior (negative attitude, condescending attitude, boastful attitude, mentoring relationships, dishonesty and insincerity, ethical violations, regressive behavior) and by the field of manifestation (social, economic, political, cultural, psychological). The article describes the peculiarities of conflict management in the hotel and restaurant business, which are caused by a large number of interested parties, emotional tension, a variety of cultures and communications, and the presence of guests.
Keywords: conflict; conflict management; conflict theories; conflict generators; conflicts in the hotel and restaurant business